Assessment and care for non-medical risk factors in current antenatal health care. Issue 10 (October 2015) - Vos, Amber A.; Leeman, Annemiek; Waelput, Adja J.M.; Bonsel, Gouke J.; Steegers, Eric A.P.; Denktaş, Semiha
Abstract Objective this study aims to identify current practice in risk assessment, current antenatal policy and referral possibilities for non-medical risk factors (lifestyle and social risk factors), and to explore the satisfaction among obstetric caregivers in their collaboration with non-obstetrical caregivers. Design cross-sectional study Setting Dutch antenatal care system Participants community midwives from 139 midwifery practices and gynaecologists, hospital-based midwives, and trainees in obstetrics from 38 hospitals. Measurements and findings results were analysed with χ2 tests and unpaired t-tests. Caregivers universally screened upon lifestyle risk factors (e.g. smoking or drug use), whereas the screening for social risk factors (e.g. social support) was highly variable. As national guidelines are absent, local protocols were reported to be used for screening on non-medical risk factors in more than 40%. Caregivers stated multidisciplinary protocols to be a prerequisite for assessment of non-medical risk factors. Only 22% of the caregivers used predefined criteria to define when patients should be discussed multidisciplinary. Conclusion despite their relevance, non-medical risk factors remain an underexposed topic in antenatal risk factor screening in both the community and hospital-based care setting. Implications for practice Structural antenatal risk assessment for non-medical risk factors with subsequent consultation opportunities is advocated, preferably based on a multidisciplinary guideline.